Membuat Aplikasi Informasi Adat Istiadat di Indonesia Berbasis Android (Information Technology and Telematics, 2014)
Abstract This shift in cultural development in Indonesia is very visible, it is because of globalization that permeates many aspects of life in Indonesia. It is intended to be able to learn the Indonesian culture from an early age without compromising the delivery of an interesting way to keep them interested in learning and not get bored. Customs is the set of social norms that has long existed and has become a habit (tradition) in the community.The method used to create or develop new software is the prototype model. This method is a systems development method is used to solve the problem of misunderstanding between the user and the analyst that arise as a result of the user not able to clearly define their needs.Keywords: Culturally, Android